2011
DOI: 10.1016/j.molcel.2011.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide Regulation of 5hmC, 5mC, and Gene Expression by Tet1 Hydroxylase in Mouse Embryonic Stem Cells

Abstract: SUMMARY DNA methylation at the 5-position of cytosine (5mC) in the mammalian genome is a key epigenetic event critical for various cellular processes. The Ten-eleven translocation (Tet) family of 5mC-hydroxylases, which convert 5mC to 5-hydroxymethylcytosine (5hmC), offers a way for dynamic regulation of DNA methylation. Here we report that Tet1 binds unmodified C, 5mC- or 5hmC-modified CpG-rich DNA through its CXXC domain. Genome-wide mapping of Tet1 and 5hmC reveals mechanisms by which Tet1 controls 5hmC and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

35
554
3
8

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 565 publications
(600 citation statements)
references
References 33 publications
35
554
3
8
Order By: Relevance
“…One prediction is that TET proteins may activate the expression of their targeted genes via their role in active DNA demethylation. However, genome-wide analysis of 5hmC distribution reveals that TET1 has dual functions in transcriptional regulation because it both enhances and inhibits the expression of some genes in mESCs [16][17][18][19]. TET1 is highly expressed in mESCs that accumulate relatively high levels of 5hmC, while 5hmC levels are significantly decreased after mESC differentiation [7].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…One prediction is that TET proteins may activate the expression of their targeted genes via their role in active DNA demethylation. However, genome-wide analysis of 5hmC distribution reveals that TET1 has dual functions in transcriptional regulation because it both enhances and inhibits the expression of some genes in mESCs [16][17][18][19]. TET1 is highly expressed in mESCs that accumulate relatively high levels of 5hmC, while 5hmC levels are significantly decreased after mESC differentiation [7].…”
mentioning
confidence: 99%
“…Downregulation of TET proteins by RNAi decreases the accumulation of 5hmC but increases 5mC. These results suggest a dynamic regulation of 5hmC by TET proteins [16][17][18][19]. Using various chromatin immunoprecipitation methods combined with high-throughput DNA sequencing, several laboratories analyzed the genome-wide distribution of 5hmC and TET1 binding sites [16][17][18][19].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although mC and hmC are recognized by common DNA binding proteins, they also have modification-specific binders (Spruijt et al 2013), thereby providing a potential mechanism for the differential effects on gene expression between mC and hmC (Xu et al 2011). Additionally, TET enzymes may prefer CG sites (Hu et al 2013) which raises the intriguing possibility that mCH may be resistant to oxidation and elimination.…”
Section: Nature and Regulation Of Dna Modificationsmentioning
confidence: 99%
“…Recent studies have shown that the status of DNA methylation at some regions in the gene body may be the consequence of a dynamic balance between methylation and hydroxymethylation or demethylation [17][18][19]. Moreover, rather than being actively transcribed or completely silenced, many genes are transcribed at different levels in tissues.…”
Section: Current Status Of Dien and Aden Network Researchmentioning
confidence: 99%